Impact of COVID‐19 on an Australian intensive care unit: lessons learned from South Australia. Issue 9 (6th August 2020) - Nadkarni, Aniket; Alderson, Steven; Collett, Luke; Maiden, Matthew; Reddi, Benjamin; Sundararajan, Krishnaswamy
Abstract: The scale of the COVID‐19 pandemic represents unprecedented challenges to healthcare systems. We describe a cohort of 18 critically ill COVID‐19 patients – to our knowledge the highest number, in a single intensive care unit in Australia. We discuss the complex challenges and dynamic solutions that concern an intensive care unit pandemic response. Acting as the State's COVID‐19 referral hospital, we provide local insights to consider alongside national guidelines.